The mathematical description of process of heat exchange particles of oil shale and ash the coolant in the semi-coking conditions in a rotating drum reactor installation with solid heat carrier - A. A. Selivanov; P. A. Batrakov; A. N. Markin; I. A. Vdovenko; O. V. Afanaseva (Известия высших учебных заведений: Проблемы энергетики)
The article deals with the modeling of heat transfer process in a drum reactor of a semi-coking unit of oil shale with a solid coolant between ash and shale particles in the conditions of constant separation of vapor-gas products. The dominant role of the convective component of the process is revealed and the curves of heating of shale particles are obtained taking into account the endothermic effect. It is established that the smallest fraction of fuel warms up within 30-60 seconds and further serves as a source of heat for other fractions. In the interval of 400-600 seconds, the heating of the largest fraction is completed. The further stay of the shale mixture in the reactor is caused by the lagging rate of the thermal decomposition process from heat exchange, and the temperature decrease by 20-250C by the presence of the endothermic effect of the decomposition of organic matter.